REFLOTATION OF MT. ISA ZINC CONCENTRATE AFTER SO2 LEACH TREATMENT - Yigit, E.; Saridede, M. N.; Ozcimen, D. (TAYLOR & FRANCIS INC, 2012)
Laboratory flotation tests were carried out on the SO2 leaching residues of zinc concentrates of Mt. Isa lead-zinc concentrator. In the evaluation of these tests grades, recoveries and separation index values of the metallic elements are used. Separation index value of a metallic element is a new concept proposed in this paper and is useful in the evaluation of any concentration process. In the bulk concentrates obtained after flotation tests, the grades, recoveries, and separation index values of silver were around 900-1000 ppm, 18-20%, and 17-19, respectively.
Keywords: flotation; leaching; residues; separation index; SO2 gas; SPHALERITE; ACTIVATION; COPPER; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing